FIGURATIVE SPEECH ANALYSIS IN HELENA NATASHA’S POETRY “DREAMS SPELLED IN POETRY” - Ratna Sari Dewi; Saiful Anwar Matondang; M Manugeren (Universitas Putera Batam, 2026)
Poetry, as a form of literary expression, plays a significant role in conveying complex emotions and abstract ideas through imaginative language. This study aims to analyze the use of figurative speech in Helena Natasha’s poetry collection Dreams Spelled in Poetry, which explores themes of dreams, identity, and personal aspirations. The research is significant in providing a deeper understanding of how figurative language contributes to meaning-making and emotional expression in contemporary poetry. This study employs a qualitative descriptive approach as proposed. The data were collected through documentation techniques focusing on poetic lines containing figurative expressions. The analysis is based on theory of figurative speech, which classifies twelve types of figurative language. The data were analyzed using the interactive model, including data condensation, data display, and conclusion drawing. The findings reveal that 402 instances of figurative language were identified, with metaphor (68%) and personification (14%) as the most dominant types. These results indicate that Helena Natasha predominantly employs metaphorical and humanizing expressions to convey emotional depth and abstract meaning. The study concludes that figurative language plays a central role in enhancing the aesthetic and interpretative value of poetry.